2016
DOI: 10.1039/c6lc00488a
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic spinning of silk fibers and in situ cell encapsulation

Abstract: In situ embedding of sensitive materials (e.g., cells and proteins) in silk fibers without damage presents a significant challenge due to the lack of mild and efficient methods. Here, we report the development of a microfluidic chip-based method for preparation of meter-long silk fibroin (SF) hydrogel fibers by mimicking the silkworm-spinning process. For the spinning of SF fibers, alginate was used as a sericin-like material to induce SF phase separation and entrap liquid SFs, making it possible to shape the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Among various fiber-form biomaterials 17 21 , microfluidic spinning microfibers have been widely used in biomedical applications such as tissue engineering 22 25 and wound dressing 26 due to their extraordinary features such as their ability to guide cell growth 27 29 , their large surface-to-volume ratios 30 32 , and the various ways their surfaces can be modified. Among the diverse approaches for fabricating microfibers, microfluidics has recently attracted much attention because of its advantages in providing simple, rapid, and spatiotemporal control over the composition of the material along the microfiber, and the ability of this method to encapsulate a cell in the microfiber 22 , 24 , 33 , 34 . However, the importance of the mechanical properties of resulting fibers exposed to physiological conditions has been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Among various fiber-form biomaterials 17 21 , microfluidic spinning microfibers have been widely used in biomedical applications such as tissue engineering 22 25 and wound dressing 26 due to their extraordinary features such as their ability to guide cell growth 27 29 , their large surface-to-volume ratios 30 32 , and the various ways their surfaces can be modified. Among the diverse approaches for fabricating microfibers, microfluidics has recently attracted much attention because of its advantages in providing simple, rapid, and spatiotemporal control over the composition of the material along the microfiber, and the ability of this method to encapsulate a cell in the microfiber 22 , 24 , 33 , 34 . However, the importance of the mechanical properties of resulting fibers exposed to physiological conditions has been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…The LIVE/DEAD assay confirmed that the encapsulated HepG2 cells kept a high survival rate for more than 7 d . Similarly, Cheng et al introduced a Y‐shaped PDMS‐based microfluidic device to generate cell‐laden hydrogel fibers, using the SF/alginate solution mixed with L929 fibroblast cells as the core flow, the CaCl 2 aqueous solution as the sheath flow (Figure b) . The results of LIVE/DEAD assay showed that cells in the SF/alginate fibers remained alive with a high viability for a long period (>12 d).…”
Section: Microfluidic Spinning Of Nfsmentioning
confidence: 99%
“…b) Schematic of the biomimetic spinning of SF/alginate fibers using a Y‐shaped PDMS‐based microfluidic device. Reproduced with permission . Copyright 2016, Royal Society of Chemistry.…”
Section: Microfluidic Spinning Of Nfsmentioning
confidence: 99%
“…Despite the existence of many fabrication methods for microfluidic wet spinning devices, none of them can fulfill all the above-mentioned requirements. For instance, soft lithography has been widely used in a laboratory setting for producing microfluidic chips [8][9][10], but involves tedious procedures including mask design and fabrication, plasma bonding, as well as time-consuming slab alignment [11,12]. Alternatively, subtractive manufacturing techniques, such as laser cutting and micro-milling, can shorten the device production procedure [13][14][15][16], but usually require extensive device engineering [14].…”
Section: Introductionmentioning
confidence: 99%